Dielectric polymeric compositions for improved electrical properties of flexible electronics - Tahalyani J.; Khanale M.; Kandasubramanian B. (My University, 2025)
The current work aims toward enhancement in electrical properties with different polymer compositions, like blending of polymer solution of polyvinyl alcohol (PVA) and polyaniline (PANI) with gold nanoparticles (AuNP). Material Studio software and Flory Hugin’s model verified the immiscibility of PVA/PANI polymers, added with AuNP to get bifunctional conducting and insulating surface by spin coating. FT-IR and FESEM confirmed the agglomeration of AuNP particles over the surface. When polyvinyl pyrollidone was used as a second binder along with PVA for solution casting with modifying amount of PANI, it showed 1000 times increment in AC conductivity at room temperature with superior dielectric constant in the semiconducting region. © 2018 Elsevier Inc. All rights reserved.